2016
DOI: 10.4172/2157-7145.1000332
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse in Fayoum Governorate, Egypt (2010-2014)

Abstract: Background and Objective: Child abuse is not an uncommon issue for pediatrics; rather, it is a major public health worry all over the world. An apparent form of maltreatment with children is child sexual abuse (CSA), which has negative consequences on both the short and long-term health consequences, apparent in both physical and mental disorders. This study is particularly important to determine the demographic and medico-legal aspects of sexual abuse of children in Fayoum Governorate, Egypt, which has clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Ecchymosis (6.1%) was the most frequent wound in CSA cases. These results are in agreement with previous studies of Saint-Martin et al (2014) and Waheb (2016) who reported that the medico-legal examination did not reveal traumatic injuries in whole body except gentiala. Bruises represented the most common type of injury.…”
Section: 4%supporting
confidence: 93%
See 1 more Smart Citation
“…Ecchymosis (6.1%) was the most frequent wound in CSA cases. These results are in agreement with previous studies of Saint-Martin et al (2014) and Waheb (2016) who reported that the medico-legal examination did not reveal traumatic injuries in whole body except gentiala. Bruises represented the most common type of injury.…”
Section: 4%supporting
confidence: 93%
“…Sex crimes are complex and multidimensional over the past few decades, child sexual abuse has gained public attention and become one of the most high-profile crimes. CSA is considered one of the greatest threats to a child's well-being, and safety prevention and dealing with this situation is no easy task (Waheb et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Abo-Seria et al (2019) reported absence of signs general violence in the majority (87.7%) of CSA victims, with bruises were the most frequent (6.1%). Likewise, the medico-legal examination did not reveal any traumatic injuries in whole body in other studies Saint-Martin et al (2014) and Waheb (2016). Alternatively, the series by White and McLean (2006) and Küçüker (2008) reported predominance of general violence with of traumatic injuries in the whole body of their victims Medico-legal examination of vulvo-vaginal and perineal regions in the female victims exposed to rape, attempted rape and mixed vaginal-anal assault (98cases) revealed that both recent and old hymen tears were detected in 40.8%of cases.…”
Section: Discussionmentioning
confidence: 61%
“…Also, Hwa et al (2010) recorded the presence of anal skin abrasions and/or laceration in about 57.1% of the male victim, while an anal mucosal tear was present in 53.1% of female victims and 57.1% of male victims [2]. Mawaheb et al (2016) revealed that the perianal signs were found in 80% of the victims, though they were absent in 20% of them [13].…”
Section: Discussionmentioning
confidence: 99%
“…Mwaheb et al (2016) and Celbis et al(2006), which revealed that a most of the victims were related to the rural areas[13][14]. On contrary, the studies conducted by of El-Elemi et al (2011) and Sherif et al (2018) demonstrated that most of the female sexual assault cases were from urban areas [7, 10].…”
mentioning
confidence: 99%